Effect of solid concentration on biogas production through anaerobic digestion of rapeseed oil cake. Issue 11 (3rd June 2021) - Deepanraj, B.; Senthilkumar, N.; Ranjitha, J.
ABSTRACT: Solid concentration is considered as one of the most important parameters governing the anaerobic digestion process. In this present study, four solid concentration levels (10%, 15%, 20% and 25% of total solids), were tested to evaluate the effect on biogas production from rapeseed oil cake. Four laboratory scale batch reactors with 2 L volume were used for this study with a retention period of 30 days. The performance of reactors was assessed by quantifying the daily biogas production, cumulative biogas production and the degradation of total solids, volatile solids and COD. Biogas production was found to be maximum at a solid concentration of 20%, followed by 25%, 15% and 10%. The results obtained from the study were evaluated using Gompertz, modified Gompertz and Logistic models to determine the kinetic constants of the process. There were smaller differences between measured and predicted biogas production for rapeseed oil cake when using a modified Gompertz model compared with the other two models.